Thurstonella, replacement name for the Antarctic amphipod genus Clarencia K.H. Barnard, 1931 (Crustacea, Amphipoda, Thurstonellidae), preoccupied by Clarencia Sloane, 1917 (Insecta, Coleoptera, Carabidae) - Lowry, Jim; Zeidler, Wolfgang (Zootaxa, 2008)
The generic name Clarencia was originally proposed by Sloane (1917) for a genus of carabid beetles (Insecta, Coleoptera, Carabidae). It is a valid name in current use for a small endemic genus of Australian/Papua New Guinean ground beetles, recently revised by Baehr (2005). Clarencia K.H. Barnard, 1931, was established as a monotypic genus of Antarctic amphipods. Shaw (1989) and Zeidler (1994) have both redescribed Clarencia chelata K.H. Barnard, 1931. Zeidler (1994) re-diagnosed the family Clarenciidae Barnard & Karaman, 1987 and set up the superfamily Clarencioidea. It was recently brought to our attention that Clarencia K.H. Barnard, 1931 is a junior homonym of Clarencia Sloane, 1917. The new name, Thurstonella, is proposed to replace Clarencia K.H. Barnard, 1931. Because the type genus of the family is a junior homonym, the family group name Clarenciidae Barnard & Karaman, 1987, is replaced with Thurstonellidae, in accordance with Article 39 of the International Code of Zoological Nomenclature (1999, fourth edition).